Pinecone 1959 - Valdosta State College (Valdosta State College, 1959)
This year Valdosta State celebrated its 39th Homecoming event with one of the most gala social events of the season. The theme for the event, chosen by the Student Government Association, was Frontier Days. Miss Pam Paulk of Valdosta reigned over the weekend as Homecoming Queen. The big parade with over 35 units began Friday afternoon, and had in it many attractive floats. The Homecoming game, Friday night, kept the fans tense and excited down to the final seconds as the "Rebs" emerged victorious over Piedmont 59-57. The terrific dance Saturday night with Dean Hudson and his orchestra supplying the music and its Valentine theme will long be remembered. MISS HOMECOMING 1959 Pam Paulk Miss Homecoming surrounded by her Court on the Homecoming Float sponsored by the SGA....
A year book was published for Valdosta State College from 1925-1977, under the name The Pinecone. From 1981-1987, a yearbook was published called Milestones. Valdosta State University had three names during this period, Georgia State Womans College, 1925-1950; Valdosta State College, 1950-1993; and Valdosta State University 1993-present.
Keywords: yearbook; Americana